Build quality of groundwater wells and contamination problems - Montagnani, Fabio; Berti, Fausto; Magini, Stefano (Acque Sotterranee - Italian Journal of Groundwater, 2013)
The protection of water resources from pollution risks cannot be considered apart from the build quality of water work, particularly with regard to water wells. Its design features are essential to preserve the quality and quantity of the resource put in charge. The construction elements work well, which can lead to contamination of groundwater, are different and have different processes and pathways of contamination that are generated. The wellhead is a constructive element often overlooked but is the first vehicle of contamination of underground aquifers by infiltration surface direct from the floor bell. The breaking of the casing are then a second important element for contamination of aquifers through paths of cross-contamination. The natural aging of the works for the presence of corrosions and stray currents together with the use of materials of low resistance and their incorrect project are the main causes of this phenomenon. It is therefore important to the executive project of the casing with the relative strength checks . Another important constructive element which generates often problems of contamination of aquifers, both on the part of the infiltration surface both for interconnection between different aquifers, is cementation and more generally the isolations. Their main function is that of isolating the circuits put in charge of the well preventing mixing between aquifers separated. Are analyzed and described the main methods and materials used in conjunction with the operating procedures for the proper execution of cementation.